PERSEPSI MAHASISWA TERHADAP ETIKA BISNIS DAN ETIKA PROFESI DIPANDANG DARI SEGI GENDER (STUDI KASUS MAHASISWA AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERISTAS ISLAM MALANG) - Yulia Rahma Denita; Nur Diana; Hariri Hariri (Universitas Islam Malang, 2022)
This study aims to determine student perceptions of business and professional ethics regarding gender. The type of research used in this research is quantitative research with a descriptive approach. The quantitative research method in this study uses comparative research. The population of this study was Accounting Students, Faculty of Economics and Business, the University of Islam Malang in the 2018 batch 291 students. Determination of the sample using purposive sampling. Data analysis methods with the Independent Difference t-test. The results of the tests that have been carried out show no difference in the perception of male and female accounting students on business ethics and professional ethics.Keywords: perception, business ethics, professional ethics, gender.